OPTIMALISASI PERAN GURU PENDAMPING KHUSUS (GPK) DALAM MENERAPKAN PERMAINAN KOOPERATIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL ANAK DENGAN AUTISM SPECTRUM DISORDER (ASD) DI SD ISLAM AL MADANI BANJARBARU - Nauratun Nisrina; Miftahul Aula Sa’adah; Mulyani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to describe the role of the Special Assistance Teacher (GPK) in implementing cooperative games to improve the social skills of children with Autism Spectrum Disorder (ASD) at SD Islam Al Madani Banjarbaru, and identify the challenges or obstacles faced in its implementation. Cooperative play is a learning approach that focuses on interaction and cooperation between individuals, which has been proven effective in stimulating the social skills of children with special needs, including children with ASD who generally experience barriers in social communication and mutual interaction. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects in this study were GPKs who assisted students with ASD in the inclusive learning environment of SD Islam Al Madani Banjarbaru. The results showed that GPK has an important role that includes facilitating a safe and supportive play environment, accompanying children intensively during activities, providing emotional support, guiding the process of social interaction in the game, assessing children's social needs, and evaluating the development of social skills periodically. However, in its implementation, the GPK also faces various challenges, such as the GPK must adapt the game to the characteristics of ASD children, challenges in fostering children's interest in cooperative games, and limited learning facilities and media. Nevertheless, the support from the school, collaboration with class teachers and parents, as well as the enthusiasm and high concern of the GPK were the main supporting factors for the success of the intervention. This study concludes that the active role of GPK in implementing cooperative games contributes positively to the improvement of ASD children's social skills, and needs further support from both policy aspects and strengthening teacher capacity